Virtual reality technologies for learning English: an example of using Immerse - Lobanova, Olga; Fedorova, Elena; Vobolevich, Alena; Minakova, Polina; Rybakova, Lyudmila (Institute of Advanced Engineering and Science, 2024)
This study aims to examine the effectiveness of using the Immerse virtual reality technology as an additional tool for learning English. The sample consisted of 120 students randomly selected from the lists of third-year students studying English as a foreign language according to their bachelor’s degree curriculum. The overall sample was divided into two groups. Immerse was a virtual reality technology used for training in an experimental group for three months. The results showed that in the experimental group, there was a significant difference between the pre-test and the post-test (0.35<0.05). In the control group, there were no relevant changes. In particular, these data show that the experimental group significantly outperformed the control group in terms of academic performance in English. However, some of the tasks that tested writing skills showed unsatisfactory results. In general, although virtual reality (VR) does not affect students’ writing skills, its use is crucial for their long-term memorization.